2019
DOI: 10.1038/s41598-019-38489-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Deficiency is Associated with Dysbiosis and Changes in Metabolic Function of the Mouse Intestinal Microbiome

Abstract: Serotonin transporter (SERT) plays a critical role in regulating extracellular availability of serotonin (5-HT) in the gut and brain. Mice with deletion of SERT develop metabolic syndrome as they age. Changes in the gut microbiota are being increasingly implicated in Metabolic Syndrome and Diabetes. To investigate the relationship between the gut microbiome and SERT, this study assessed the fecal and cecal microbiome profile of 11 to 12 week-old SERT+/+ and SERT−/− mice. Microbial DNA was isolated, processed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 63 publications
3
53
0
Order By: Relevance
“…We also found that the proportion of Enterococcus was significantly increased in the ADHD group, and Enterococcus has been reported to be closely related to neurotransmitter release. One study demonstrated that Enterococcus abundance is significantly increased in mice lacking the 5-HT transporter (Singhal et al, 2019); deficiency of this transporter can lead to decreased 5-HT levels, which is related to ADHD onset (Wang et al, 2018). Interestingly, a study showed Enterococcus could lead to excessive intestinal conversion of levodopa (the first-line treatment for Parkinson's disease) into dopamine, however, peripheral dopamine cannot penetrate the BBB to enter the CNS, thus reducing the effectiveness of levodopa (Maini Rekdal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the proportion of Enterococcus was significantly increased in the ADHD group, and Enterococcus has been reported to be closely related to neurotransmitter release. One study demonstrated that Enterococcus abundance is significantly increased in mice lacking the 5-HT transporter (Singhal et al, 2019); deficiency of this transporter can lead to decreased 5-HT levels, which is related to ADHD onset (Wang et al, 2018). Interestingly, a study showed Enterococcus could lead to excessive intestinal conversion of levodopa (the first-line treatment for Parkinson's disease) into dopamine, however, peripheral dopamine cannot penetrate the BBB to enter the CNS, thus reducing the effectiveness of levodopa (Maini Rekdal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that the Coriobacteriaceae family, which is involved in urolithin B production, is positively associated with total cholesterol and LDL levels and is a potential CVD risk biomarker (Romo‐Vaquero, et al , ). Other molecules, such as indoleamine 2,3‐dioxygenase, serotonin (5‐HT) and NAPEs, are also correlated with gut microbiota changes that alter lipid absorption or lipid metabolism, consequently linking the gut microbiota to cardiometabolic phenotypes (Laurans, et al , ; May‐Zhang, et al , ; Singhal, et al , ). Melatonin improves lipid metabolism, and the potential mechanism is related to gut microbiota reprogramming, especially with respect to Bacteroides‐ and Alistipes‐ mediated acetic acid production (Yin, et al , ).…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…The arachidonic acid has an immune-enhancing effect [64]. Enteroendocrine cells within the mucosal lining of the gut synthesize and secrete a number of hormones including 5-HT, which have regulatory roles in key metabolic processes such as insulin sensitivity, glucose tolerance, fat storage, and appetite [61,65,66]. Gutderived 5-HT in shaping gut microbiota composition in relation to susceptibility to colitis, identifying 5-HT-microbiota axis as a potential new therapeutic target in intestinal inflammatory [67].…”
Section: Discussionmentioning
confidence: 99%